1992
DOI: 10.1111/j.1749-6632.1992.tb17123.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Folate Adequacy as Determined by Homocysteine Levela

Abstract: The classic vitamin deficiency syndromes are the result of acute and severe enzymatic disfunction resulting from extremely low vitamin levels. In recent years, more interest has been focused on less severe deficiencies that may lead to chronic disease. One such relationship is that of folate and homocysteine (HCY). Folate is a cofactor for methionine synthetase, an enzyme that recycles HCY into methionine.' If folate levels are insufficient, HCY levels rise. Elevated HCY levels have been associated with the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 3 publications
2
21
0
Order By: Relevance
“…Hence, the importance of the ®ndings of this primary care study which show that the higher the initial homocysteine, the greater the folate effect, even with relatively small increases in folic acid intake. Published work also indicates that there is a decrease in the slope of the inverse relationship between homocysteine and serum folate when folate concentrations are in the upper half of the reference range (Molgaard et al, 1992;Lewis et al, 1992;Selhub et al, 1993;Jacobsen et al, 1994;Pancharuniti et al, 1994). This bimodal inverse relationship is con®rmed here, as the plasma homocysteine decrease following supplementation Homocysteine responsiveness to folate CJ Schorah et al was largely con®ned to those who were initially within the lower tertile of the serum folate range ( Table 2).…”
Section: Discussionmentioning
confidence: 53%
“…Hence, the importance of the ®ndings of this primary care study which show that the higher the initial homocysteine, the greater the folate effect, even with relatively small increases in folic acid intake. Published work also indicates that there is a decrease in the slope of the inverse relationship between homocysteine and serum folate when folate concentrations are in the upper half of the reference range (Molgaard et al, 1992;Lewis et al, 1992;Selhub et al, 1993;Jacobsen et al, 1994;Pancharuniti et al, 1994). This bimodal inverse relationship is con®rmed here, as the plasma homocysteine decrease following supplementation Homocysteine responsiveness to folate CJ Schorah et al was largely con®ned to those who were initially within the lower tertile of the serum folate range ( Table 2).…”
Section: Discussionmentioning
confidence: 53%
“…In that case, the prevalence of low plasma folate in our population would increase from 1% to 10.5%. In a similar approach Lewis et al (1992) suggested a cut-off value of 15 nmol=l. Brouwer et al (1998) established a cut-off value of 10 nmol=l using also an oral methionine tolerance test and folic acid supplementation, resulting in 31% being folate deficient.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed this is likely given that in the United States fortification of enriched cereal grain products had commenced 2 y prior to the publication of their study (Lawrence et al, 1999). With reference to the microbiological assay, there appears to be a clear inverse association between tHcy and plasma folate when plasma folate is less than 15 nmol=l and a less robust relationship when plasma folate exceeds this level (Lewis et al, 1992). While this appears to be the most likely explanation of the differences in response of tHcy between the study by Malinow et al (1998) and our own study, it should also be noted that participants in the Malinow study were older individuals with ischaemic heart disease while those in the Ward et al (1997) study and our own study were younger and free of clinical disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that one of the potentially important clinical and public health benefits of folate, namely its association with tHcy and vascular disease, appears to require a level of serum folate (around 15 nmol=l, Lewis et al, 1992), which can be achieved with a very small amount of supplemental folic acid. This observation is relevant to national policies regarding fortification.…”
Section: Discussionmentioning
confidence: 99%